Pengembangan desain furnitur kardus modular dengan memanfaatkan fitting berbasis pencetakan 3D - Achmad, Abdul Gafur Maulana; Djati, Imam Damar (Institut Seni Indonesia Yogyakarta, 2025)
Modular cardboard furniture is becoming increasingly popular as a practical, economical, and efficient solution for temporary use. However, existing modular cardboard furniture generally relies on a stacking system without a secure locking mechanism, making it less stable in various configurations. Fittings as connector components play a crucial role in enhancing the modularity and stability of cardboard furniture. This study aims to design and develop 3D-printed fittings to optimize the joints between modular cardboard furniture units. In this study, single-wall flute C cardboard was used to develop a modular cardboard shelf unit in the form of a cube with dimensions of 35 × 35 × 35 cm, with holes at each corner to accommodate the fittings. Structural strength testing showed that the module could withstand loads of up to 18 kg before experiencing buckling at the pressure-receiving surface. The fittings were developed using 3D printing technology with the Fused Deposition Modeling (FDM) method, utilizing a MakerBot Replicator 2 printer and MakerBot PLA filament. Finite Element Analysis (FEA) was used to analyze the structural strength of the fittings. The development resulted in 17 modular fitting variants, consisting of edge connectors and corner connectors, with flexible configurations. With these fittings, the configuration of modular cardboard furniture becomes more flexible, stable, and adaptable to user needs. This study contributes to the development of a 3D-printed joint system for cardboard furniture, offering a more optimized solution compared to conventional methods.